2021
DOI: 10.1136/bcr-2021-242472
|View full text |Cite
|
Sign up to set email alerts
|

Postural orthostatic tachycardia syndrome (POTS) occurring during treatment for breast cancer

Abstract: Postural orthostatic tachycardia syndrome (POTS) is a common condition of orthostatic intolerance in response to changes in position. We report a case of a middle-aged woman presenting with a new onset of POTS likely due to chemotherapy for treatment of breast cancer. She was started on a trial of a beta blocker, which was effective in controlling her symptoms and heart rate. The objective of this report was to encourage clinicians to consider POTS as a differential diagnosis, while managing patients with symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…Cardiac autonomic neuropathy in cancer survivors can present in the form of orthostatic hypotension, postural orthostatic tachycardia syndrome, and tachycardia [16]. However, in the current study, the basal HR and BP of ALL patients immediately after chemotherapy were found to be lower as compared to the controls.…”
Section: Discussioncontrasting
confidence: 79%
“…Cardiac autonomic neuropathy in cancer survivors can present in the form of orthostatic hypotension, postural orthostatic tachycardia syndrome, and tachycardia [16]. However, in the current study, the basal HR and BP of ALL patients immediately after chemotherapy were found to be lower as compared to the controls.…”
Section: Discussioncontrasting
confidence: 79%